Psychological influences on distance estimation in a virtual reality environment - Takahashi, Kohske; Meilinger, Tobias; Watanabe, Katsumi; Bülthoff, Heinrich H. (Frontiers in Human Neuroscience, 2013)
Studies of embodied perception have revealed that social, psychological, and physiological factors influence space perception. While many of these influences were observed with real or highly realistic stimuli, the present work showed that even the orientation of abstract geometric objects in a non-realistic virtual environment could influence distance perception. Observers wore a head mounted display and watched virtual cones moving within an invisible cube for 5 s with their head movement recorded. Subsequently, the observers estimated the distance to the cones or evaluated their friendliness. The cones either faced the observer, a target behind the cones, or were oriented randomly. The average viewing distance to the cones varied between 1.2 and 2.0 m. At a viewing distance of 1.6 m, the observers perceived the cones facing them as closer than the cones facing a target in the opposite direction, or those oriented randomly. Furthermore, irrespective of the viewing distance, observers moved their head away from the cones more strongly and evaluated the cones as less friendly when the cones faced the observers. Similar distance estimation results were obtained with a 3-dimensional projection onto a large screen, although the effective viewing distances were farther away. These results suggest that factors other than physical distance influenced distance perception even with non-realistic geometric objects in a virtual environment. Furthermore, the distance perception modulation was accompanied by changes in subjective impression and avoidance movement. We propose that cones facing an observer are perceived as socially discomforting or threatening, and potentially violate an observer's personal space, which might influence the perceived distance of cones.